1987
DOI: 10.1093/oxfordjournals.aje.a114573
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Ischemic Heart Disease in the Belgian Physical Fitness Study: Physical Fitness Rather Than Physical Activity?

Abstract: Occupational and leisure time physical activity and conventional risk factors were determined in the Belgian Physical Fitness Study, a prospective study of 2,363 healthy male factory workers who were aged 40-55 years at entry in 1976-1978 and who were followed for five years. Physical fitness, defined as the interpolated physical working capacity at heart rate 150 beats per minute, was measured in 2,109 subjects. In this subgroup, there were 31 myocardial infarctions and sudden deaths. Smoking, physical fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 0 publications
4
30
0
3
Order By: Relevance
“…Two studies compared the role of LTPA and physical ®tness in the prevention of fatal or nonfatal CHD. 18,41 In their study, Hein et al 18 concluded that, among sedentary men, being very ®t does not provide protection against CHD and all-cause mortality; however un®t and sedentary men had a higher risk of CHD than un®t and active men.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared the role of LTPA and physical ®tness in the prevention of fatal or nonfatal CHD. 18,41 In their study, Hein et al 18 concluded that, among sedentary men, being very ®t does not provide protection against CHD and all-cause mortality; however un®t and sedentary men had a higher risk of CHD than un®t and active men.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of OPA were associated with a reduced risk of CVD in some prospective population-based studies (9-15) but not others (10,13,(16)(17)(18)(19)(20)(21) or were associated with an increased CVD risk (22)(23)(24)(25)(26)(27)(28) and, in one study, depending on level of fitness (29). A few studies showed differential effects, with LTPA being protective and OPA having no effect (20,30), LTPA having an effect only among persons with low levels of OPA (14), or LTPA constituting a CVD risk (23), especially among persons with high levels of OPA indicating an interaction between OPA and LTPA (28).…”
mentioning
confidence: 95%
“…While the beneficial effects of leisure-time physical activity on the circulatory system are relatively well established, the literature about the health effects of occupational physical activity remains inconsistent (5). Higher levels of occupational physical activity were associated with a reduced risk of CVD in some prospective population-based studies (6)(7)(8)(9)(10)(11), showed no association in others (7,12,8,(13)(14)(15)(16)(17), or were associated with an increased CVD risk (18)(19)(20)(21). A few studies showed…”
mentioning
confidence: 99%